2009
DOI: 10.1021/ol900126q
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Group and Solvent Control of Stereo- and Chemoselectivity in Glucal 3-Carbamate Amidoglycosylation

Abstract: In the Rh 2 (OAc) 4 -catalyzed amidoglycosylation of glucal 3-carbamates, anomeric stereoselectivity and the extent of competing C3-H oxidation depend on the 4O and 6O protecting groups. Acyclic protection permits high α-anomer selectivity with further improvement in less polar solvents, while electron-withdrawing protecting groups limit C3-oxidized byproducts. Stereocontrol and bifurcation between alkene insertion and C3-H oxidation reflect an interplay of conformational, stereoelectronic, and inductive facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 60 publications
0
35
0
1
Order By: Relevance
“…However, high selectivity for the a-anomer could be achieved following extensive optimisation of the reaction solvent system and protecting group strategy. [39] Liu and co-workers have recently discovered that this rhodium(II) methodology can be made highly diastereoselective for the formation of a-and b-anomers of trans 1,2-aminoglycosides 47 and 48 by strategically tethering the sulfonamide at the C(6) or C(4) position of the glycal (Scheme 19). [40,41] It was reported that a wide range of oxygen nucleophiles, including carboxylic acids, can be added to the aziridine intermediates to react with high stereoselectivity.…”
Section: Rhodium-catalysed Reactionsmentioning
confidence: 99%
“…However, high selectivity for the a-anomer could be achieved following extensive optimisation of the reaction solvent system and protecting group strategy. [39] Liu and co-workers have recently discovered that this rhodium(II) methodology can be made highly diastereoselective for the formation of a-and b-anomers of trans 1,2-aminoglycosides 47 and 48 by strategically tethering the sulfonamide at the C(6) or C(4) position of the glycal (Scheme 19). [40,41] It was reported that a wide range of oxygen nucleophiles, including carboxylic acids, can be added to the aziridine intermediates to react with high stereoselectivity.…”
Section: Rhodium-catalysed Reactionsmentioning
confidence: 99%
“…In parallel to these developments, catalytic nitrene transfer has been reported as an alternative for the development of regioselective oxyamination reactions. Pioneering studies from the groups of Rojas [11] and Padwa [12] have shown that dirhodium(II) complexes are the catalysts of choice to perform the oxyamination of glycal-and indolylcarbamates (Scheme 1 a). Liu et al have found that sulfamates are also competent nitrene precursors for this transformation.…”
mentioning
confidence: 99%
“…We focused on the use of p -methoxybenzyl-(PMB) urea. Deprotection by oxidative cleavage with either CAN 14 or DDQ 15 resulted in complex mixtures and no formation of the desired product. However, hydrolysis in acidic media 16 (TFA, 60 °C) resulted in clean conversion to the desired target compounds, providing access to products containing hydrogenation-sensitive functional groups and/or heteroarenes (Table 3).…”
mentioning
confidence: 99%